Early T-Cell Precursor Leukemia Has a Higher Risk of Induction-Related Infection among T-Cell Acute Lymphoblastic Leukemia in Adult - Kangyu Huang; Min Dai; Qiuli Li; Nannan Liu; Dainan Lin; Qiang Wang; Xuan Zhou; Zhixiang Wang; Ya Gao; Hua Jin; Xiaoli Liu; Qifa Liu; et al. (Mediators of Inflammation)
Background. Infections are an important cause of morbidity and mortality for acute lymphoblastic leukemia (ALL). However, the reports regarding risk factors of induction-related infection are roughly unknown/limited in adult T-ALL during induction chemotherapy. Methods. We performed a retrospective cohort study for the prevalence and risk predictors of induction-related infection among consecutive T-ALL patients (N=97) enrolled in a PDT-ALL-LBL clinical trial. Of 97 patients with T-ALL enrolled in the trial, 46 were early T-cell precursor (ETP) ALL and 51 were non-ETP ALL. Results. When compared with non-ETP, ETP ALL subtype was characterized with lower neutrophil count (1.35×109/L vs. 8.7×109/L, P<0.001) and lower myeloid percentage in the bone marrow (13.35% vs. 35.31%, P=0.007). Additionally, ETP ALL had longer neutropenia before diagnosis (P<0.001), as well as during induction chemotherapy (P<0.001). Notably, the ETP cohort experienced higher cumulative incidence of clinically documented infections (CDI; 33.33%, P=0.001), microbiologically documented infections (MDI; 45.24%, P=0.006), resistant infection (11.9%, P=0.013), and mixed infection (21.43%, P=0.003), respectively, than those of the non-ETP cohort. Furthermore, multivariable analysis revealed that T-ALL mixed infection was more likely related to chemotherapy response (OR, 0.025; 95% CI 0.127-0.64; P=0.012) and identified myeloid percentage as a predictor associated with ETP-ALL mixed infection (OR, 0.915; 95% CI 0.843-0.993; P=0.033), with ROC-defined cut-off value of 2.24% in ETP cohorts. Conclusions. Our data for the first time demonstrated that ETP-ALL characterized with impaired myelopoiesis were more susceptible to induction-related infection among T-ALL populations.